Prevalence of early postpartum depression and associated risk factors among selected women in southern Malawi: a nested observational study - E Moya; G Mzembe; M Mwambinga; Z Truwah; R Harding; R Ataide; Leila M Larson; J Fisher; S Braat; SR Pasricha; MN Mwangi; KS Phiri (BMC, 2023)
Abstract Background The birth of a child should be a time of celebration. However, for many women, childbirth represents a time of great vulnerability to becoming mentally unwell, a neglected maternal morbidity. This study aimed to determine the prevalence of early postpartum depression (PPD) and its associated risk factors among women giving birth at health facilities in southern Malawi. Identifying women vulnerable to PPD will help clinicians provide appropriately targeted interventions before discharge from the maternity ward. Method We conducted a nested cross-sectional study. Women were screened for early PPD using a locally validated Edinburgh Postpartum Depression Scale (EPDS) as they were discharged from the maternity ward. The prevalence of moderate or severe (EPDS ≥ 6) and severe (EPDS ≥ 9) PPD was determined, including 95% confidence intervals (CI). Data on maternal age, education and marital status, income source, religion, gravidity, and HIV status, among others, were collected during the second trimester of pregnancy, and obstetric and infant characteristics during childbirth were examined as potential risk factors for early PPD using univariable and multivariable logistic regression analyses. Results Data contributed by 636 women were analysed. Of these women, 9.6% (95% CI; 7.4-12.1%) had moderate to severe early PPD using an EPDS cut-off of ≥ 6, and 3.3% (95% CI; 2.1-5.0%) had severe early PPD using an EPDS cut-off of ≥ 9. Multivariable analyses indicated that maternal anaemia at birth (aOR; 2.65, CI; 1.49-4.71, p-value; 0.001) was associated with increased risk for moderate and/or severe early PPD, while live birth outcome (aOR; 0.15, 95% CI; 0.04-0.54, p-value; 0.004), being single compared to divorced/widowed (aOR; 0.09, 95% CI; 0.02-0.55, p-value; 0.009), and lower education level (aOR; 0.36, 95% CI; 0.20-0.65, p-value; 0.001) were associated with decreased risk. Being HIV positive (aOR; 2.88, 95% CI; 1.08-7.67, p-value; 0.035) was associated with severe PPD only. Conclusion The prevalence of early PPD was slightly lower in our selected sample compared to previous reports in Malawi and was associated with maternal anaemia at birth, non-live birth, being divorced/widowed and HIV-positive status. Therefore, health workers should screen for depressive symptoms in women who are at increased risk as they are discharged from the maternity ward for early identification and treatment.